Plaubelia burmensis, a new name for P. perinvoluta (Pottiaceae), with special reference to the phylogenetic relationship between Plaubelia and Hyophila - Mao, Lihui; Zuo, Qin; He, Si; Zhang, Li (Phytotaxa, 2014)
The new name Plaubelia burmensis (Pottiaceae) is proposed for the species currently recognized as Desmatodon burmensis and for replacing the illegitimate name P. perinvoluta. The species is reported here first time from China. A detailed description and illustrations for the species as well as a diagnostic key to the currently recognized three species of Plaubelia are provided. A phylogenetic analysis based on four DNA loci from three genomic compartments (cp rps4, mt nad5, nr ITS and nr 26S) shows that Plaubelia species are nested within the Trichostomoideae of the Pottiaceae, sister to Hyophila involuta.